Joint response of surface subsidence and strong mine earthquake under high-positioned and thick-hard strata in deep coal mine - Guangchao Zhang; Guangyou Zhang; Guanglei Zhou; Zhaoyun Zhang; Junpeng Ma; Kai Lv; Shuiquan Chen; Zhi Qu (Scientific Reports)
Abstract Multiple active mining faces and extensive excavations under thick-hard strata in deep coal mines result in frequent strong mine earthquakes, often accompanied by significant surface subsidence deformation. Understanding the specific law of surface movement and the spatiotemporal distribution response to intense mine earthquakes is crucial for effectively preventing and mitigating dynamic disasters in deep mines. Utilizing the key layer theory, the intricate strata of the Yingpanhao Coal Mine are systematically delineated, drawing upon the engineering context of working faces 2201 and 2202 within the Ordos Chemical Co., Ltd., a subsidiary of the Shandong Energy Group. Field investigations are conducted to analyze the law of surface subsidence associated with multi-working face extraction within deep thick-hard strata, as well as to elucidate the spatiotemporal distribution characteristics of strong mine earthquakes. Furthermore, the interplay between law of surface subsidence and the spatial distribution of strong mine earthquakes is investigated, revealing a cohesive relationship between these phenomena. The research findings of this study provide certain references for the pre-control of surface subsidence and strong mine earthquakes during multiple working face and large space mining under thick-hard strata in deep coal mine with similar engineering geological conditions.